2022
DOI: 10.3389/fsurg.2022.935765
|View full text |Cite
|
Sign up to set email alerts
|

Construction of prognostic signature of patients with oral squamous cell carcinoma based on pyroptosis-related long non-coding RNAs

Abstract: Background and objectiveOral squamous cell carcinoma (OSCC) is the most common malignant tumor in the head and neck, and its morbidity and mortality are increasing year by year. Changes in key genes are thought to be closely related to the occurrence and development of OSCC. Pyroptosis is an inflammatory form of programmed cell death that has been implicated in malignancies and inflammatory diseases. Changes in the expression of long noncoding RNAs may also affect tumorigenesis and progression. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Among the selected studies, 46 studies evaluated ferroptosis , 22 studies focused on pyroptosis [28,33,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83], 8 studies on necroptosis [84][85][86][87][88][89][90][91] and 5 studies on other types of cell death [92][93][94][95][96]. One study [28] explored both ferroptosis and pyroptosis, Among the selected studies, 46 studies evaluated ferroptosis , 22 studies focused on pyroptosis [28,33,[64][65][66][67][68][69][70][71][72][73]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the selected studies, 46 studies evaluated ferroptosis , 22 studies focused on pyroptosis [28,33,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83], 8 studies on necroptosis [84][85][86][87][88][89][90][91] and 5 studies on other types of cell death [92][93][94][95][96]. One study [28] explored both ferroptosis and pyroptosis, Among the selected studies, 46 studies evaluated ferroptosis , 22 studies focused on pyroptosis [28,33,[64][65][66][67][68][69][70][71][72][73]…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings revealed that 5-fluorouracil (5-FU) treatment increased NLRP3 expression in OSCC, which mediated drug resistance. It was also proven Methods of pyroptosis inhibition are gaining the attention of the scientific community [65,69,74,154]. Yang et al [69] highlighted that extracellular vesicles derived from bitter melon led to a significant decrease in the expression of NLRP3, reducing OSCC resistance to 5-FU treatment.…”
Section: Pyroptosismentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that a pyroptosis-related gene signature was prognostic for HNSC patient 13 . Several recent studies performed bioinformatics analyses and found that the pyroptosis-related signature was prognostic for the level of immune cell infiltration benefit to immunotherapies in OSCC 14 16 . Other evidences were also provided about the role of pyroptosis in the development and treatment of OSCC 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%